Innovative character of development of modern organization of the use of the land (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The innovative reference points of development of organization of the use of land are reflected in the article, reasonable, that shows a soba organization of the use of land. Reasonable tasks and maintenance of organization of the use of land. It is marked that organization of the use of lands finds the practical introduction in form charts, projects of organization of the use of land other land documentation. It is said, that the innovativeness of organization of the use of land consists in setting of norms of relations between public authorities and organs of local self-government, by subjects of ménage on the land.Offered principles on that development of projects of contour-reclamative organization of territory must be based. It is marked that the innovativeness of organization of the use of land consists in setting of norms of relations between public authorities and organ of local self-government, by the subjects of ménage on land. It is well-proven that projects of organization of the land are the obligatory conditions of production on the land. Exposed aspects on that formalization of process of development of charts of organizations of the use of land must be based.
Keywords: organization of the use of land, projects of contour-reclamative organization of territory, innovative character, charts of organization of the use of land, projects of organization of the use of land.